Abattoir-based study of Salmonella prevalence in pigs at slaughter in Great Britain. (2nd September 2021) - Martelli, F.; Oastler, C.; Barker, A.; Jackson, G.; Smith, R. P.; Davies, R.
Abstract: Consumption of pork and pork products can be associated with outbreaks of human salmonellosis. Salmonella infection is usually subclinical in pigs, and farm-based control measures are challenging to implement. To obtain data on Salmonella prevalence, samples can be collected from pigs during the slaughter process. Here we report the results of a Great Britain (GB) based abattoir survey conducted by sampling caecal contents from pigs in nine British pig abattoirs during 2019. Samples were collected according to a randomised stratified scheme, and pigs originating from 286 GB farms were included in this survey. Salmonella was isolated from 112 pig caecal samples; a prevalence of 32.2% [95% confidence interval (CI) 27.4–37.4]. Twelve different Salmonella serovars were isolated, with the most common serovars being S . 4, [5], 12:i:-, a monophasic variant of Salmonella Typhimurium (36.6% of Salmonella- positive samples), followed by S. Derby (25.9% of Salmonella- positive samples). There was no significant difference compared to the estimate of overall prevalence (30.5% (95% CI 26.5–34.6)) obtained in the last abattoir survey conducted in the UK (2013). Abattoir-based control measures are often effective in the reduction of Salmonella contamination of carcasses entering the food chain. In this study, the effect of abattoir hygiene practices on the prevalence of Salmonella on carcasses was not assessed. Continuing Salmonella surveillance at slaughter is recommended to assess effect of farm-based and abattoir-based interventions and to monitor potential public health risk associated with consumption of Salmonella- contaminated pork products.